Dynamics of Panax ginseng Rhizospheric Soil Microbial Community and Their Metabolic Function - Li, Yong (Hindawi Publishing Corporation, 2014)
The bacterial communities of 1- to 6-year ginseng rhizosphere soils were characterized by culture-independent approaches, random amplified polymorphic DNA (RAPD), and amplified ribosomal DNA restriction analysis (ARDRA). Culture-dependent method (Biolog) was used to investigate the metabolic function variance of microbe living in rhizosphere soil. Results showed that significant genetic and metabolic function variance were detected among soils, and, with the increasing of cultivating years, genetic diversity of bacterial communities in ginseng rhizosphere soil tended to be decreased. Also we found that Verrucomicrobia, Acidobacteria, and Proteobacteria were the dominants in rhizosphere soils, but, with the increasing of cultivating years, plant disease prevention or plant growth promoting bacteria, such as Pseudomonas, Burkholderia, and Bacillus, tended to be rare.